Arthritis & arthroplasty - edited by Francis H. Shen; Christopher I. Shaffrey
The Spine―a volume in the new Arthritis and Arthroplasty series―offers expert guidance on everything from patient selection and pre-operative planning to surgical approaches and techniques. Francis H. Shen and Christopher I. Shaffrey present clear, evidence-based coverage detailing which technology and methodology is best for each patient. Access discussions of debates on anterior versus posterior approaches for the surgical management of cervical myelopathy, indications for thoracoscopic surgery, options for minimally invasive surgery (MIS) in degenerative spinal conditions, and more. Explore the role for evolving technologies and non-fusion techniques for the management of various spinal pathologies and view expertly narrated video demonstrations of surgical techniques